Improved NOE fitting for flexible molecules based on molecular mechanics data – a case study with S-adenosylmethionine - Bame, Jessica; Hoeck, Casper; Carrington, Matthew J.; Butts, Craig P.; Jäger, Christof M.; Croft, Anna K. (Royal Society of Chemistry, 2018)
The use of molecular dynamics (MD) calculations to derive relative populations of conformers is highly sensitive to both timescale and parameterisation of the MD. Where these calculations are coupled with NOE data to determine the dynamics of a molecular system, this can present issues if these populations are thus relied upon. We present an approach that refines the highly accurate PANIC NMR methodology combined with clustering approaches to generate conformers, but without restraining the simulations or considering the relative population distributions generated by MD. Combining this structural sampling with NOE fitting, we demonstrate, for S-adenosylmethionine (aqueous solution at pH 7.0), significant improvements are made to the fit of populations to the experimental data, revealing a strong overall preference for the syn conformation of the adenosyl group relative to the ribose ring, but with less discrimination for the conformation of the ribose ring itself.